«Soft power» of South Korea in Kazakhstan (Journal of Oriental Studies, 2017)
In today’s world there is increasing importance of «soft» levers of influence on the global community. Many countries are interested in brend-building and improving the image of their country on the world stage. In this regard, each country is trying to create its own model of «soft power.» In particular, remarkable success of South Korean model of «soft power» and, as a consequence, the increase of attractiveness of South Korea in the world. As part of this work we studied example of the South Korean «soft power»mechanisms’ influence in the Republic of Kazakhstan.